Preference of Women for Gestational Diabetes Screening Method According to Tolerance of Tests and Population Characteristics - Raets, Lore; Vandewinkel, Marie; Van Crombrugge, Paul; Moyson, Carolien; Verhaeghe, Johan; Vandeginste, Sofie; Verlaenen, Hilde; Vercammen, Chris; Maes, Toon; Dufraimont, Els; Roggen, Nele; De Block, Christophe; et al. (Frontiers in Endocrinology, 2021)
Aims: To determine the preferred method of screening for gestational diabetes mellitus (GDM). Methods: 1804 women from a prospective study (NCT02036619) received a glucose challenge test (GCT) and 75g oral glucose tolerance test (OGTT) between 24-28 weeks. Tolerance of screening tests and preference for screening strategy (two-step screening strategy with GCT compared to one-step screening strategy with OGTT) were evaluated by a self-designed questionnaire at the time of the GCT and OGTT. Results: Compared to women who preferred one-step screening [26.2% (472)], women who preferred two-step screening [46.3% (834)] were less often from a minor ethnic background [6.0% (50) vs. 10.7% (50), p=0.003], had less often a previous history of GDM [7.3% (29) vs. 13.8% (32), p=0.008], were less often overweight or obese [respectively 23.1% (50) vs. 24.8% (116), p<0.001 and 7.9% (66) vs. 18.2% (85), p<0.001], were less insulin resistant in early pregnancy (HOMA-IR 8.9 (6.4-12.3) vs. 9.9 (7.2-14.2), p<0.001], and pregnancy outcomes were similar except for fewer labor inductions and emergency cesarean sections [respectively 26.6% (198) vs. 32.5% (137), p=0.031 and 8.2% (68) vs. 13.0% (61), p=0.005]. Women who preferred two-step screening had more often complaints of the OGTT compared to women who preferred one-step screening [50.4% (420) vs. 40.3% (190), p<0.001]. Conclusions: A two-step GDM screening involving a GCT and subsequent OGTT is the preferred GDM screening strategy. Women with a more adverse metabolic profile preferred one-step screening with OGTT while women preferring two-step screening had a better metabolic profile and more discomfort of the OGTT. The preference for the GDM screening method is in line with the recommended Flemish modified two-step screening method, in which women at higher risk for GDM are recommended a one-step screening strategy with an OGTT, while women without these risk factors, are offered a two-step screening strategy with GCT.